Syringes for intraocular administration: Systematic review - Pascual Carrasco, Ángela; Espadas García, Isabel; Ramírez López, Ana; Selva Otaolaurruchi, Juan (Farmacia hospitalaria : organo oficial de expresion cientifica de la Sociedad Espanola de Farmacia Hospitalaria, 2024)
The off-label use in clinical practice of non-approved syringes for intravitreal drug administration has resulted in the detection of silicone oil drops in the vitreous of some patients. This situation derives from the lack of approved syringes for intraocular use in the Spanish market. The aim of this work is to review the use of syringes for intraocular administration, as well as to search for alternatives that meet the legal requirements for these unmet needs. A systematic review was performed following the PRISMA 2020 Guidelines by searching PubMed with the descriptors: "silicone" AND "syringes" AND ("intraocular" OR "intravitreal") and filtering all existing publications from January 2006 to December 2023, including all those articles dealing with silicone oil release in intravitreal injections and analysing the possible consequences. Sixty-eight results were found, 23 of which were excluded because they did not deal with the subject under study, leaving a total of 45 articles for the systematic review. These were classified according to the conclusions obtained in 4 groups: the adverse reactions produced by silicone, the administration technique, the physicochemical aspects of silicone release, and the characteristics of the medical device. After reviewing the current manufacturers and technical data sheets of commercialized syringes, the existing syringes for this use have been collected, finding two that will probably be commercialized in Spain at the beginning of 2024: Zero Residual™ 0.2 ml SiO-free and VitreJect® Ophthalmic. From the results obtained, it can be interpreted that the use of syringes and needles with silicone for intravitreal use is a concern for health professionals due to the implications and consequences that may arise in patients, the most important being adverse reactions, so it is necessary to have silicone-free syringes on the market that are specific for intraocular use. Safety and legality in the use of intraocular syringes and needles is essential to guarantee ocular integrity and patient health.